TIL O`RGANISHNING INSON HAYOTIDAGI O`RNI - Xakimjonova Sevinch O`lmasboy Qizi (TADQIQOTLAR, 2026)
Abstract This explores the importance of language learning in human life focusing on mental , article social, cultural, and professional dimensions. The research is based on the author’s critical observations, comparative analysis, and personal findings rather than simple literature review. The relationship between language and thinking is examined through the ideas of classical scholars and modern linguists. Furthermore, the role of foreign language learning in the era of globalization and its impact on personal development, flexible, and social integration are highlighted. The findings show that language learning plays a critical role in cognitive development and professional advantage.